PENINGKATAN PENGETAHUAN PEMASARAN BAGI PELAKU USAHA KECIL DAN MENENGAH DI DESA JOHO KECAMATAN MOJOLABAN KABUPATEN SUKOHARJO - Erni Widiastuti; Sarsiti; Asih Handayani (SURAKARTA ABDIMAS JOURNAL, 2023)
Abstract The objective of implementing the outreach program in the context of community service activities with the theme "Increasing Marketing Knowledge for Small and Medium Enterprises" (UKM) is to overcome the challenges often faced by SMEs in developing their businesses in an era of increasingly tight market competition. The activity method is carried out using two methods: (a) Presentation (the material presented in community service activities is about knowledge of marketing concepts as well as marketing knowledge in business management, creating value for customers, and achieving superior performance in the form of power point) (b) Questions and answers and discussion of the results of the implementation of the extension program from Small and Medium Enterprises (UKM) actors in Joho Village, Mojolaban District, Sukoharjo Regency. The results of outreach activities are expected to provide a strong understanding of marketing concept knowledge and marketing knowledge in managing Small and Medium Enterprises (SMEs) businesses, creating value for customers, and achieving superior performance. Apart from that, this activity is expected to help Small and Medium Enterprises (SMEs) to compete better and support local economic growth Keywords: counseling, Increasing Marketing Knowledge, SME Business Actors